Effect Evaluation of Sahtak bi Sahnak, a Lebanese Secondary School-Based Nutrition Intervention: A Cluster Randomised Trial - Said, Liliane; Gubbels, Jessica S.; Kremers, Stef P. J. (Frontiers in Nutrition, 2022)
Abstract Objective: To evaluate the effectiveness of Sahtak bi Sahnak on dietary knowledge and adherence to dietary guidelines in Lebanese adolescents Design/setting: A cluster randomised controlled trial was conducted in public and private secondary schools located in urban and rural regions in Lebanon Participants: Sixteen secondary schools including 1572 adolescents were randomly assigned to the intervention (n=739) or control group (n=833). Intervention: Sahtak bi Sahnak is an educational school-based intervention dedicated to improving dietary adherence to nutritional guidelines, increasing the level of dietary knowledge, and preventing the development of obesity during adolescence. It was systematically designed based on the Intervention Mapping framework. The total length of the intervention was around seven educational sessions, until all of the 11 lessons were covered. Each education session lasted 20 to 40 minutes. Main Outcome Measures: Dietary knowledge and adherence levels were measured at baseline and post-intervention using validated questionnaires. Statistical Analysis: Multivariate multilevel regression models were used to examine intervention effects on outcomes, controlled for background characteristics (i.e., age, gender, location, type of school, grade, BMI z-score). Results: The intervention group showed significant improvements in total dietary knowledge (B=12.74, p< 0.001) and intake of healthy items (B=1.89, p< 0.001), compared to the control group. Intake of unhealthy items decreased significantly (B= - 1.43, p< 0.001), compared to the control group. These results were adjusted for age, gender, type of school, location, BMI z-score, study group, and score at baseline. Conclusions and Implications: Sahtak bi Sahnak is an effective and culturally appropriate school-based intervention for targeting diet among a variety of Lebanese adolescents.